المشاكل التي تواجه القطاع الصناعي في الجزائر - بودرامة, مصطفى; قصاص, الطيب (University of Eloued جامعة الوادي, 2017)
يدرس هذا البحث المشاكل التي تقف كحاجز وتواجه تطور القطاع الصناعي الجزائري، وقد خضعت المؤسسات الصناعية إلى مجموعة من إجراءات الإصلاح الداخلي منذ مطلع الثمانينيات إلى يومنا هذا، والتي لم تنجح وكلفت خزينة الدولة مبالغ ضخمة تكفي لإنشاء حظيرة صناعية جديدة، وبقي هذا القطاع يعاني من ضعف كبير في مساهمة الصناعات التحويلية في القيمة المضافة الإجمالية هذا من جهة، وانخفاض قيمة الصادرات الصناعية نتيجة ضعف آلية الجهاز الصناعي الجزائري من جهة أخرى، وعدم مقدرته على إنتاج منتجات ذات جودة عالية تستطيع المنافسة محليا ودوليا. Abstract: This research studies problems that stands as a barrier and faces the development of Algerian industrial sector, the which has undergone to a set of procedures for internal reform since the beginning of the 1980 to the present day, which did not succeed and cost the state huge money for the establishment of a new industrial zone, this sector remained suffering from a great weakness in the contribution of manufacturing industries in the total value added and, on the other hand, the decline in the value of the industrial exports as a result of the weakness of the mechanism of the Algerian industrial system , and inability to produce high-quality products can compete locally and internationally
Problems facing the industrial sector in Algeria
مجلة رؤى المجلد السابع العدد 12
Keywords: القطاع الصناعي، الصناعات التحويلية، الصناعات الاستخراجية، القيمة المضافة، الصادرات الصناعية; the industrial sector, manufacturing, extractive industries, the added value, industrial exports. (JEL) Classification : L16. L52